137k views
0 votes
I need the answer plz​

I need the answer plz​-example-1
User Tyrelle
by
4.8k points

1 Answer

2 votes

Answer:

see explanation

Explanation:

If (x - 1) is a factor then f(1) = 0

Given

f(x) = x³ - 13x² + 32x - 20 , then

f(1) = 1³ - 13(1)² + 32(1) - 20

= 1 - 13 + 32 - 20

= 0

Since f(1) = 0 then (x - 1) is a factor

Using Synthetic division

1 | 1 - 13 32 - 20

↓ 1 - 12 20

-----------------------------

1 - 12 20 0 ← remainder

quotient = x² - 12x + 20 = (x - 2)(x - 10)

Then

x³ - 13x² + 32x - 20 = (x - 1)(x - 2)(x - 10) ← in factored form

User Wassim Sboui
by
5.4k points